Millisecond Digital Stop-watch / Mohd Hasri Hamzah and Nooreastmali Idris - Hamzah, Mohd Hasri; Idris, Nooreastmali (2002)
“Time is gold”, “Time is sharper than sword” and “Time change everything”. This three aphorism can tell us how important time in our lives. Watch is the device to determine the time. It’s included to determine date, hour, minute and second. Even to comparing how fast thing moves between two points, time is useful in this case. That’s why we create the device called ‘Millisecond Digital Stop-watch’ This stopwatch is suitable to measure the time for a thing moves between two points. And this stopwatch can read until 0.001 seconds. Actually, this stopwatch is widely use in sports arena like Formula One Racing and Sprint that can give us die exact result. Win or loose is consider to the time difference. So, we can proof that time is very important although even only 0.001 second